QUALITY OF WORK LIFE: ENHANCING PERFORMANCE AND SATISFACTION IN BANKING SECTOR - Annie Riya Michael.C; M. Gnana Muhila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the relationship between Quality of Work Life (QWL), Job Satisfaction (JS), and Job Performance (JP) among bank employees in the Kanniyakumari district. Using a conceptual model and data collected from 282 respondents, the research confirms that QWL significantly impacts JS and JP, with JS acting as a mediator between QWL and JP. Structural equation modeling revealed strong correlations between these variables, emphasizing their interconnected nature. Practical implications highlight the importance of fostering supportive work environments, promoting work-life balance, and recognizing employee performance to enhance satisfaction and productivity. Limitations, such as sample size and cross-sectional design, indicate the need for future research with larger, diverse samples and additional variables. This study underscores the strategic role of QWL in driving organizational success in the banking sector.